Estudos sobre a biologia de flebótomos, vetores de Leishmanioses - Lutzomyia intermedia Lutz & Neiva, 1912 e Lutzomyia longipalpis Lutz & Neiva, 1912 - em condições experimentais - Rangel, Elizabeth Ferreira (1985)
To improve our knowledge on the breeding and bchaviour of sandflies in captivity, we established closed colonies of Lutzomyia intermedia and L. longipalpis, vectors of leishmaniases in the state of Rio de Janeiro. Data are here presented on the first four generations of each species. Besides the introduction of some alterations in the known breeding techniques, the following observations were carried out: the survival and feeding capacity of females after the first oviposition; duration and survival rate in each immature stage of development – egg, larva and pupa; food preference of larvae and adults; influence of environmental factors – temperature, humility and light intensity – on the behaviour of each species; life span and tolerance of females to the absence of blood meal; resistance of immature stages to low ternperature and to immersion in water. The l ife span of the two species was similar; both survived the first oviposition and were able to feed again on blood; both developed better when the females fed on hamster than on man, dog or bird; previous feeding on sugar was not necessary to induce a blood meal. The immature stages of both species resisted to immersion in water for up to 1 hour and to low ternperature (5ºc) for 1 to 6 hours. Mortality was greater in the egg and first larval stages (I and II) and lowest in the pupal stage.